The Impact of Product Innovation and Corporate Image on Customer Loyalty: The Mediating Role of Customer Satisfaction - Yolanda Novi Dwiyanti; Euis Soliha (Yayasan Riset dan Pengembangan Intelektual, 2024)
Motorcycles are now not only a means of productive transportation for Indonesian people, but motorbikes have become part of a hobby and lifestyle. This study aims to determine the effect of product innovation and corporate image on customer loyalty with customer satisfaction as a mediating variable (a study on customers of PT. Astra Motor Mranggen Demak). The data used in this study are primary data collected through a survey. The sample used in this study was 100 Honda motorcycle customers at PT. Astra Motor Mranggen Demak. The method used to take samples is Purposive Sampling. Based on the results of data analysis, it was found that product innovation has a positive effect on customer satisfaction, corporate image has a positive effect on customer satisfaction, product innovation has no effect on customer loyalty, corporate image has a positive effect on customer loyalty, customer satisfaction has a positive effect on customer loyalty, customer satisfaction mediates the effect of product innovation on customer loyalty, customer satisfaction mediates the effect of corporate image on customer loyalty.